1970
DOI: 10.1159/000252482
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Absorption of Trivalent and Hexavalent Chromium (<sup>51</sup>Cr) Through Excised Human and Guinea Pig Skin

Abstract: The percutaneous absorption rate of trivalent (CrCl3) and hexavalent (Na2CrO4) chromium through excised human and guinea pig whole skin was determined by an isotope method (disappearance measurements). No difference in absorption between the compounds was observed. Thus, the lower absorption of CrCl3, obtained with the same method in vivo, could not be verified. The ratios between the in vivo/in vitro rates for CrCl3 were lower than 1; for Na2Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
3

Year Published

1974
1974
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 9 publications
0
3
0
3
Order By: Relevance
“…Chromium is a known sensitizer causing allergic contact dermatitis in industries such as construction (caused by cement) and leather tanning. , A number of studies reported chromium permeation indicating an increase in permeation through the skin with an increase in concentration. ,,− The influence of a counterion such as chloride was shown, with higher permeability of chromium in a salt form (e.g., CrCl 3 )…”
Section: Metalsmentioning
confidence: 99%
“…Chromium is a known sensitizer causing allergic contact dermatitis in industries such as construction (caused by cement) and leather tanning. , A number of studies reported chromium permeation indicating an increase in permeation through the skin with an increase in concentration. ,,− The influence of a counterion such as chloride was shown, with higher permeability of chromium in a salt form (e.g., CrCl 3 )…”
Section: Metalsmentioning
confidence: 99%
“…Tai yra saugi riba, labai sumažinanti įsijautrinimo chromui riziką. Šešiavalentis chromas turi didžiausią įtaką kontaktinės alergijos ir alerginio kontaktinio dermatito išsivystymui [9][10][11]. Mūsų tyrime chromo kiekis ant pirštų tarp administracijos darbuotojų ir darbininkų nesiskyrė.…”
Section: Pirštų Merkimo Mėginysunclassified
“…Eine der bekanntesten toxikologischen Wirkungen sind die Kontaktekzeme und Dermatiden, die sowohl in einigen Berufsgruppen, wie Zement-und Bauarbeiter [6,56,571 oder in der leder-und chromverarbeitenden Industrie [%I, als auch bei allgemeinem Chromkontakt moglich sind [33,[59][60][61]. Eine akute toxische firomvergiftung erzeugt eine Hepatitis [62].…”
Section: Toxikologische Wirkungunclassified
“…Die Resorptionsleistung der Haut ist sowohl vom pH-Wert als auch der chemischen Form des Chroms abhangig. So steigt die Resorptionsquote des Chroms durch die Haut deutlich ab einem pH-Wert iiber 7 an [31, 321 und wenn es in sechswertiger Form vorliegt[33]. Das Blut dient als Transportmedium des resorbierten Chroms [23]; es ist dort an das Siderophilin gekoppelt[34].…”
unclassified